Sudan : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Sudan. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that Sudan is facing significant domestic and international constraints and large macroeconomic imbalances despite efforts made toward macroeconomic stability and growth. Although good harvests boosted growth to close to 5 percent in 2015, external imbalances widened owing to low commodity export prices, expansionary policies, and insufficient exchange rate adjustment. The terms-of-trade shock widened the current account deficit to 6 percent of GDP in 2015. The budget deficit widened to 1.9 percent of GDP owing to shortfalls in oil revenue. Inflation, which had been contained to 12.6 percent at end-2015, rose to 16.5 percent in July 2016. The outlook is subject to significant downside risks.